TMET-33. ELONGATION CONTROL OF MRNA TRANSLATION SUPPORTS GROUP 3 MEDULLOBLASTOMA ADAPTATION TO NUTRIENT DEPRIVATION. (14th November 2022) - Delaidelli, Alberto; Yao, Betty; Negri, Gian Luca; Huang, Yue Zhou; Huang, Albert; Leprivier, Gabriel; Sorensen, Poul
Abstract: Group 3 affiliation and MYC genetic amplification are associated with poor life expectancy and substantial morbidity in children suffering from medulloblastoma (MB). However, the high metabolic demand induced by MYC-driven transformation sensitizes MYC-overexpressing MB to cell death under conditions of nutrient deprivation (ND). Additionally, MYC-driven transformation is known to promote mitochondrial oxidative phosphorylation (OXPHOS). We previously reported that eukaryotic Elongation Factor Kinase 2 (eEF2K), the master regulator of mRNA translation elongation, promotes survival of MYC-overexpressing tumors under ND. Interestingly, eEF2K is overexpressed in MYC-driven MB and our preliminary proteomics data highlight large-scale alterations in OXPHOS components affecting eEF2K deficient MB cells. We therefore hypothesized that eEF2K activity is required for the selective translation of mRNAs needed for efficient OXPHOS, and for the progression of MYC-driven MB. We performed Multiplexed enhanced Protein Dynamic Mass Spectrometry in eEF2K knockdown MYC-overexpressing D425 MB cells to identify mRNAs selectively translated upon eEF2K activation. Messenger RNAs encoding multiple (9 out of 10 detected) components of the mitochondrial OXPHOS pathway are selectively translated upon eEF2K activation. Inactivation of eEF2K by genetic KO leads to the disassembly of electron transport chain (ETC) complexes I-IV without affecting mRNA levels of their respective components. Consistently, eEF2K KO MB cells display decreased mitochondrial membrane potential and 20% increased proton leak thorough the mitochondrial membrane. In addition, eEF2K inactivation results in increased Group 3 MB cell death under ND and doubles survival of MB bearing mice fed with calorie restricted diets (p< 0.05). Control of mRNA translation elongation by eEF2K is critical for mitochondrial ETC complex assembly and efficient OXPHOS in MYC-overexpressing MB, likely representing an adaptive response by which MYC-driven MB cells cope with acute metabolic stress. Future therapeutic studies will aim to combine eEF2K inhibition with caloric restriction mimetic drugs as eEF2K activity appears critical under metabolic stress conditions.